Analysis of Tourist Attractions, Amenities and Accessibility to Tourist Visit Decisions Mediated by Digitalization Promotion - Surya, Elfitra Desy; Felani, Kiki Farida; Felani, Virdyra Tasril; Andriani, Anggi (Cattleya Darmaya Fortuna, 2023)
The purpose of this research is to test and analyze the impact MSME development to improve the image of the Mutiara Beach destination as culinary tourism with digital-based promotions in the City of Pari Serdang Bedagai and to test and analyze the impact of MSME development for enhancing the image of the Mutiara Beach destination as a culinary tour through tourist satisfaction with digital-based promotions in Pari Serdang Bedagai City. The hypotheses in this study are cognitive image, affective image and unique image positive and significant effect simultaneously to enhance the image pearl beach destination as a culinary tour with digital-based promotions in Kota Pari is different, and cognitive image, affective image and unique image partially positive and significant effect to improve the image of the destination Mutiara Beach as a culinary tour through tourist satisfaction with promotions digital based City of Pari Serdang Bedagai. The materials to be used in this study are: Quantitative Materials, where the Quantitative Material in this study relates to the data describe variable X1 cognitive image, variable X2 affective image, variable X3 unique image, Y1 (Mediation Variable) tourist satisfaction, and for the variable Y2 is destination image. The research location was carried out at the pearl beach of Pari City Serdang Bedagai District, North Sumatra Province. Data analysis used are: Quantitative Analysis consisting of Path Analysis (Path Analysis) with a population of 300 consumers and with using the slovin formula obtained a sample of 171 people.